Analysis of Pipe Diameter Variation and Lamp Load on Centrifugal Pump Performance as a Generator Driving Turbine - Musabbikhah Musabbikhah; Ryan Dhana Dyaksa (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
As the population grows, the demand for energy increases, especially from non-renewable resources. Many countries are turning to renewable energy sources such as water to meet this demand. Water from a certain height can drive a turbine generator by converting potential energy into mechanical energy in the form of shaft rotation, which is transmitted to the generator and then converted into electrical energy. This study aims to analyse variations in pipe diameter and lamp load on the performance of a centrifugal pump as a turbine driving a generator. The research method was an experiment in which the pipe diameter was varied as 1/2, ¾, 1, and 1.5 inches, and the lamp load was varied as 5, 10, 15, and 20 W. Pump performance includes specific speed, rotor power, and shaft power. The results of this study show that the performance of the centrifugal pump as a driving turbine, the highest is at a pipe diameter of 1.5 inches, which produces a specific speed of 207.59 rpm at a power load of 5 W, rotor power of 2002 watts at a load of 20 W, and shaft power of 9509.50 watts at a load of 20 W. By regression analysis, the highest specific speed was obtained by the formula y=223.16-2.9063x with a correlation coefficient of r=0.989. The rotor power formula was y=57.093+98.045x with a correlation coefficient of r=0.999, while the resulting shaft power formula was y=271.19+465.72x with a correlation coefficient of r=0.999. Thus, a strong positive relationship exists between diameter and lamp load on specific speed, rotor power, and shaft power to generate electrical energy sources in turbine axle pumps.